SARS-CoV-2 viral-load distribution reveals that viral loads increase with age: a retrospective cross-sectional cohort study. (8th September 2021) - Euser, Sjoerd; Aronson, Sem; Manders, Irene; van Lelyveld, Steven; Herpers, Bjorn; Sinnige, Jan; Kalpoe, Jayant; van Gemeren, Claudia; Snijders, Dominic; Jansen, Ruud; Schuurmans Stekhoven, Sophie; van Houten, Marlies; et al.
Abstract: Background: Describing the SARS-CoV-2 viral-load distribution in different patient groups and age categories. Methods: All results from first nasopharyngeal (NP) and oropharyngeal (OP) swabs from unique patients tested via SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) collected between 1 January and 1 December 2020 predominantly in the Public Health Services regions Kennemerland and Hollands Noorden, province of North Holland, the Netherlands, were included in this study. SARS-CoV-2 PCR crossing-point (Cp)-values were used to estimate viral loads. Results: In total, 278 455 unique patients were tested, of whom 9.1% ( n  = 25.374) were SARS-CoV-2-positive. PCRs performed by Public Health Services ( n  = 211 914), in which sampling and inclusion were uniform, revealed a clear relation between age and SARS-CoV-2 viral load, with especially children aged <12 years showing lower viral loads than adults (β: –0.03, 95% confidence interval: –0.03 to –0.02, p  < 0.001), independently of sex and/or symptom duration. Interestingly, the median Cp-values between the >79- and <12-year-old populations differed by more than four PCR cycles, suggesting an ∼16-fold difference in viral load. In addition, the proportion of children aged <12 years with a low load (Cp-value >30) was higher compared with other patients (31.1% vs 17.2%, p -value < 0.001). Conclusions: In patients tested by Public Health Services, SARS-CoV-2 viral load increases with age. Further studies should elucidate whether the lower viral load in children is indeed related to their suggested limited role in SARS-CoV-2 transmission. Moreover, as rapid antigen tests are less sensitive than PCR, these results suggest that SARS-CoV-2 antigen tests have lower sensitivity in children than in adults.